Charles Burnett and Dorian Gieseler Greenbaum (eds.), From Māshāʾallāh to Kepler: Theory and Practice in Medieval and Renaissance Astrology. (14th February 2019) - Carey, Hilary
Abstract : Charles Burnett and Dorian Gieseler Greenbaum (eds.), From Māshāʾallāh to Kepler: Theory and Practice in Medieval and Renaissance Astrology (Ceredigion, Wales: Sophia Centre Press, 2015), 529 pp., £35.00 (pbk), ISBN: 978-907767-06-7.